Plan estratégico de marketing para la empresa constructora inmobiliaria Jaramillo Castillo de la ciudad de Loja, 2018-2021 - Montero Jaramillo, Verónica de los Ángeles (2018)
The purpose of this research project is aimed at proposing strategies that contribute to the development of the Jaramillo Castillo Real Estate Builder, through the proper use of the resources with which the real estate agency has and that it can provide a quality service in which refers to real estate advice, allowing to meet the needs of customers. The main objective of this thesis is to present a Strategic Marketing Plan for the company Constructora Inmobiliaria Jaramillo Castillo in the city of Loja, 2018-2021, which will lead to an increase in sales and development of the same. For the realization of the present investigation the following methods were used: deductive, inductive, descriptive and analytical, techniques such as the survey applied to clients and potential clients of the real estate, direct observation, interview to the Manager-Owner and the commercial advisors which allowed to have a general knowledge of the Constructora Inmobiliaria Jaramillo Castillo in addition to determine how is the current situation of the company. In the results, the Situational Analysis was carried out, where the analysis of the National Context using the PESTE analysis with the political, economic, social, technological, ecological factors, Analysis of the Porter's Forces and the Analysis of the surveys made to the clients. and potential customers of the company, in this way allowed to find information of utmost importance for the company, thus establishing the main opportunities such as: annulment of the Organic Law to avoid speculation 6 on the value of land and taxation, interest rates The lowest referential for loans for housing acquisition is 4.98%, the bond for housing acquisition ranges from $ 4,000.00 to $ 6,000.00, mortgage loans from BIESS up to $ 200,000.00, population growth, innovation of new technologies in advertising in the real estate sector, population willing to buy and sell real estate and population who would like to use the services of the real estate company and the main threats that are: little negotiation power with customers, possible entry of new competitors, great rivalry between competitors and little impactful and boring advertising; These results were recorded in the External Factor Evaluation Matrix (EFE), which gives a weighted result of 2.67. The Competitive Analysis that was carried out was able to establish the main competitors of the real estate company for which the Competitive Profile Matrix (MPC) was made, the result of which shows that the Real Estate Developer Jaramillo Castillo has to improve and develop strategies that allow it to excel in the real estate market the score of the company is 2.70 surpassed by Podocarpus Inmobiliaria with a score of 3.05 in second place is PROINJAR Promotora Inmobiliaria Jaramillo with a score of 2.85. In the Internal Analysis, important aspects of the company being studied were taken into account, such as administrative factors, human resources, and the analysis was carried out on the Marketing Mix taking into account the service, price, promotion-advertising, place and customer service. result of the interview applied to the Manager-Owner and the commercial advisors. With the information obtained, the Internal Factors Evaluation 7 Matrix (EFI) was obtained, obtaining a weighted result of 2.61 where the strengths were established, the main ones being the following: sales personnel receive training and motivations, the price of the service It is in accordance with the competition, ease of cash payment methods and bank financing, and the main weaknesses that the company has are: decrease in sales, few commercial advisors, advertising is not evaluated, delay in the sale of real estate, no promotions are offered. In the SWOT analysis, the threats and opportunities, weaknesses and strengths were compared, which allowed the elaboration of the High Impact Matrix, where the strategies that served to propose the proposal were determined, which contains the objectives that allow the real estate company to create a competitive advantage in the real estate sector Finally, it is considered that with this Strategic Marketing Plan the Constructora Inmobiliaria Jaramillo Castillo obtains a better positioning, greater profitability and generates more sources of work. The total cost of the Strategic Marketing Plan for the year 2018 is $ 3,547.60; for the year 2019 it is $ 7,332.50; for the year 2020 it is of $ 7,731.30 and for the year 2021 it is of $ 8,129.35; giving a total of $ 26,740.75.